Gabriel z Szadka i jego Apologia pro Collegii Posnaniensis... - Andrysiak, Ewa (Biuletyn Szadkowski, 2013)
The article presents the biography of Gabriel of Szadek and his work Apologia pro Collegii Posnaniensis, de Trino et Uno Deo assertionibus, adversus Samosatenicorum Anabaptistarum animadversions (1583), which was written in response to Poznan Jesuits’ pronouncement against SZymon Budny on the matter of Holy Trinity. The author also reminds the circumstances in which this work was printed and its further history.